Average Error: 0 → 0
Time: 527.0ms
Precision: 64
\[\frac{2}{3} - \frac{1}{3}\]
\[\frac{2}{3} - \frac{1}{3}\]
\frac{2}{3} - \frac{1}{3}
\frac{2}{3} - \frac{1}{3}
double f() {
        double r284175 = 2.0;
        double r284176 = 3.0;
        double r284177 = r284175 / r284176;
        double r284178 = 1.0;
        double r284179 = r284178 / r284176;
        double r284180 = r284177 - r284179;
        return r284180;
}

double f() {
        double r284181 = 2.0;
        double r284182 = 3.0;
        double r284183 = r284181 / r284182;
        double r284184 = 1.0;
        double r284185 = r284184 / r284182;
        double r284186 = r284183 - r284185;
        return r284186;
}

Error

Try it out

Your Program's Arguments

    Results

    Enter valid numbers for all inputs

    Derivation

    1. Initial program 0

      \[\frac{2}{3} - \frac{1}{3}\]
    2. Final simplification0

      \[\leadsto \frac{2}{3} - \frac{1}{3}\]

    Reproduce

    herbie shell --seed 1 
    (FPCore ()
      :name "2/3 - 1/3"
      :precision binary64
      (- (/ 2 3) (/ 1 3)))